Optimization of energy window for different body mass index in biograph truepoint positron emission tomography imaging system - Musarudin, Marianie (2015)
Internal scattering in patient’s body is one of the key factors that leads to PET image quality degradation. This interaction affects the imaging performance in the sense of mispositioning of the annihilation position and coincidence data lost. One of the factors that determines the probability of this interaction is the patient’s body weight. In practice, the impact of scattering is worse with the increment of the patient’s body weight. Thus, optimization of scatter events contribution in the raw data prior to image reconstruction is vital as it determines the quality of PET image generated. The quality of the image, which eventually help to determine the tumor detection rate, will improve the survival rate of the cancer patient. Various methods were proposed and identified by the previous studies to minimize the contribution of both patient and detector’s scatter to the raw data. This study, was nonetheless achieved the above target through the analysis of signal processing. The aim of this study is to define the optimal energy threshold level for the different groups of patient’s body. The definition was done based on the phantom’s modeling. Various patient’s sizes in the range of 44.0 kg to 99.0 kg which yield diameters of 20 cm to 30 cm were modeled using Monte Carlo N-Particle code version 5 (MCNP5). The impact of phantom’s masses to the several measurement parameters like scatter fraction, tumor visibility and signal to noise ratio (SNR) also was tested in order to define the optimal energy threshold level for each phantom size. Various energy threshold levels were implemented on the simulated data. Evaluation of tumor SNR on the reconstructed image was the core measure used in this study. The optimal energy threshold value was defined when the maximum SNR was yielded at the respective energy window used. At the end of this study, we managed to propose an optimal energy window for the underweight, normal and obese patient. The obese phantom which lost more photons via photon scattering and attenuation thus required up to 20.00% and 27.27% larger energy window than the underweight and normal phantom respectively. These threshold values, which are 2.30% to 13.79% varies from the default energy window that commonly practiced, improves the SNR up to 1.24%. At the end of this study, we managed to propose an equation that gave correlations among the body weight, the tumor to background ratio (TBR) and the optimal energy threshold level. The derivation of this equation was done based on the data obtained in this study. The proposed equation, therefore allows definition of the optimal energy window for any condition of imaging, particularly those related to the weight of the patient’s body and TBR or standard uptake values (SUV) of the tumor.